2020
DOI: 10.3390/su122410609
|View full text |Cite
|
Sign up to set email alerts
|

Research of Attitudes toward Online Violence—Significance of Online Media and Social Marketing in the Function of Violence Prevention and Behavior Evaluation

Abstract: The main aim of this paper is to analyze attitudes toward online violence in order to identify the current state of this problem through psychosocial analysis, as well as the possibility of preventing this kind of violence through the prism of online media and social marketing. The authors developed a conceptual model and conducted an online quantitative research study. The survey was conducted among 277 respondents in Montenegro, which is a developing country and as such is experiencing transitions in many se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
3
0
3
Order By: Relevance
“…Gender-based violence in virtual space adopted different names such as gender-based online violence (GBOV) or online misogyny and myriad forms that apply the "silencing strategies" toward women (Zaman, 2021a 2021a; Thakur et al 2015). Apparently, the range of VAW online and its meaning cannot be covered by a single definition, given that it absorbs evasive and newly appearing dimensions (Musso, 2019;Melović et al 2020). The common intentions of VAW online include targeting women and girls to denigrate, embarrass and frighten them.…”
Section: Literature Search and Justification Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Gender-based violence in virtual space adopted different names such as gender-based online violence (GBOV) or online misogyny and myriad forms that apply the "silencing strategies" toward women (Zaman, 2021a 2021a; Thakur et al 2015). Apparently, the range of VAW online and its meaning cannot be covered by a single definition, given that it absorbs evasive and newly appearing dimensions (Musso, 2019;Melović et al 2020). The common intentions of VAW online include targeting women and girls to denigrate, embarrass and frighten them.…”
Section: Literature Search and Justification Of The Studymentioning
confidence: 99%
“…The common intentions of VAW online include targeting women and girls to denigrate, embarrass and frighten them. It is estimated that 80% of women face online threats daily (Henry and Powell 2016).Women of the 18-24 age range have been found as a vulnerable category in many studies whose experience of online violence, abuse, and sexual harassment is higher than that of other age groups (Melović et al 2020;Thakur et al 2015;Duggan, 2014;PRC, 2017as cited in Musso, 2019. In their study, Melović et al (2020) showed that single and divorced women are more exposed to online violence than married ones and higher academic qualifications of women decrease the chances to be victimized since educated women are cognizant of better usage of digital resources, handling private information and securing their own presence online.…”
Section: Literature Search and Justification Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Los resultados de esta investigación apoyan la evidencia, que ya ha sido destacada en estudios anteriores, acerca de la existencia de la violencia en los entornos online como una vivencia de los jóvenes y adolescentes actuales (Donoso et al, 2018;Melović et al, 2020;Rodríguez y Ballesteros, 2019). La evidencia encontrada a lo largo de la investigación sugiere que existe violencia en los juegos que utilizan el estatus femenino y la influencia de género como blanco de insultos, ataques y acoso contra las jugadoras.…”
Section: Discusión Y Conclusionesunclassified
“…Una aproximación desde el enfoque de género, al consumo de videojuegos y la situación de las jugadoras en el sector" (Santana, 2020). • Attitudes toward Online Violence-Significance of Online Media and Social Marketing in the Function of Violence Prevention and Behavior Evaluation (Melović, B., Stojanović, A. J., Backović, T., Dudić, B., & Kovačičová, 2020). El diseño final del cuestionario estuvo compuesto por 41 preguntas que ofrecen diferentes opciones de respuesta, algunas de las cuales escalas tipo Likert, y que proporcionaban información sobre diferentes categorías de investigación como:…”
Section: Metodologíaunclassified